2016
DOI: 10.1039/c6dt00769d
|View full text |Cite
|
Sign up to set email alerts
|

New sterically-hindered o-quinones annelated with metal-dithiolates: regiospecificity in oxidative addition reactions of a bifacial ligand to the Pd and Pt complexes

Abstract: An unusual reactivity of sterically hindered o-quinones with an annelated dithiete ring towards coordination at a dithiolene site has been discovered. New Pd and Pt dithiolate complexes have been synthesized. The reaction proceeds regioselectively, and the quinone site of the parent ligand is not affected even while using an excess of the metal complex. Both Pt and Pd complexes display a square planar surrounding for the metal ion and have very similar NMR, IR and UV/Vis spectra. Surprisingly, being coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Until now electrochemical studies were reported for similar systems with monodentate phosphine ligands only. [14] CV measurements indicate that compounds 4-10 undergo three transformations upon reduction. The first and the second transitions are ligand-centered, and they can be attributed to the subsequent formation of o-semiquinonate radical-anion and catecholate dianion species (Scheme 5).…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Until now electrochemical studies were reported for similar systems with monodentate phosphine ligands only. [14] CV measurements indicate that compounds 4-10 undergo three transformations upon reduction. The first and the second transitions are ligand-centered, and they can be attributed to the subsequent formation of o-semiquinonate radical-anion and catecholate dianion species (Scheme 5).…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Kuropatov et al reported the platinum complex of benzo‐1,2‐dithiete [6c,9]. We also prepared the dinuclear palladium complex upon treatment of benzo‐1,2‐diselenete 2c with tetrakis(triphenylphosphine)palladium [8].…”
Section: Introductionmentioning
confidence: 95%
“…Binding at the dithiolate coordination site is preferable for the soft Lewis acids and vice versa. Group 10 zero-valent metal tetrakis (triphenylphosphine) complexes M(PPh 3 ) 4 (M = Pd, Pt) selectively react towards dithiolene site of the ligand 68 with formation of 71 and 72 mononuclear adducts (Scheme 31) [43].…”
Section: Ss~oo Systemsmentioning
confidence: 99%
“…Binding at the dithiolate coordination site is preferable for the soft Lewis acids and vice versa. Group 10 zero-valent metal tetrakis (triphenylphosphine) complexes M(PPh3)4 (M = Pd, Pt) selectively react towards dithiolene site of the ligand 68 with formation of 71 and 72 mononuclear adducts (Scheme 31) [43]. According to the cyclic voltammetry data, coordination of a metal fragment on the dithiolene site significantly decreases the first reduction potential of free dioxolene site from −0.42 V (68) to −0.90 V (71) and −0.80 V (72).…”
Section: Ss~oo Systemsmentioning
confidence: 99%
See 1 more Smart Citation